Arduino-based Farm Feeder Helper / Nur Fareena Ezani As’ad and Noor Fadzilah Razali - As’ad, Nur Fareena Ezani; Razali, Noor Fadzilah (UiTM Cawangan Melaka Kampus Jasin, 2021)
Farmed domestic animals usually lives in cramped and filthy conditions with insufficient food, and drinks in enclosed areas. Instead of treating them as living beings, the modern industrial way in which this industry produces dairy and other animal products has turned them into mere production units. In this project, the animal will get its food based on the preset time in the programming. Other than that, it will ensure that animals in the farm will kept hydrated by providing enough water all the time inside the farm. Additionally, this project also ensures that the air inside the farm will remain fresh and clean from any unpleasant smell that have been produced by the animals inside the farm. As the result, animals in the farm will live a good life and act as the base in generating quality product in the future, as well as helping farm owners to control feeding time. This project utilizes the use of Arduino microcontroller to control the conditions in the farm by controlling proper ventilation system, feeding water level and appropriate feeding time. Both motor servo and exhaust fan are used to supply water and expel smelly odors respectively to achieve the optimal condition in the farm. Necessary informations are displayed on the Liquid Crystal Display (LCD) unit.